Correlation between central incisor eruption status and lower facial height in children aged 6-8: a cross-sectional study - Ednur, Mutiara Putri; Rahmawati, Atiek Driana; Octavia, Alfini; Medawati, Ana (Universitas Padjadjaran, 2024)
Introduction: Tooth eruption is a key indicator of growth, influencing the timely appearance of permanent teeth essential for facial aesthetics. Age and tooth eruption sequence are crucial in clinical dental health care planning. Fully erupted incisors play a significant role in facial appearance, with facial height impacting facial shape throughout growth. This study aims to analyze the correlation between the eruption status of maxillary and mandibular central incisors and lower facial height in children aged 6-8. Methods: This research used a cross-sectional approach. The study's population consisted of 225 children aged 6 to 8 years from Muhammadiyah Purwodiningratan Elementary School. Sampling was conducted using a purposive sampling strategy based on the established inclusion and exclusion criteria, resulting in 102 children being sampled. Dental impressions were taken using alginate. The lower facial height was measured as the distance from the subnasale to the menton. Eruption status was categorized with a score of 0 for teeth not erupted, 1 for partially erupted teeth, and 2 for fully erupted teeth. Spearman analysis was conducted to assess the correlation between incisor eruption status and facial height. Results: A significant correlation was found between eruption status and lower facial height (p<0.05), with significance values for tooth 11 at 0.009, tooth 21 at 0.004, tooth 31 at 0.003, and tooth 41 at 0.002. Conclusion: The eruption status of central incisors exhibits a weak positive correlation with lower facial height, with mandibular incisors showing a stronger association than maxillary incisors in children aged 6-8.